Intraventricular Conduction Disturbances After Transcatheter Aortic Valve Implantation - Shu-I Lin; Mizuki Miura; Ana Paula Tagliari; Ying-Hsiang Lee; Shinichi Shirai; Rishi Puri; Francesco Maisano; Maurizio Taramasso (Interventional Cardiology: Reviews, Research, Resources)
Despite significant improvements in transcatheter aortic valve implantation (TAVI) outcomes, periprocedural conduction disturbances, such as new-onset left bundle branch block (LBBB) and new pacemaker implantation (PMI), remain relatively frequent concerns. The development of periprocedural conduction disturbances can be explained by the proximity between the aortic valve and the conduction system. Although prior studies reported heterogeneity in PMI rates after TAVI, current evidence supports the potentially deleterious consequence of LBBB and PMI, and several predisposing factors have been reported. Therefore, new strategies to avoid conduction disturbances and to improve their management are required, particularly with the current trend to expand TAVI to a low-risk population.